The implications of contractual terms of employment for women and leadership: An autoethnographic study in UK higher education - Anne Vicary; Karen Jones (Administrative Sciences, 2017)
This article is concerned with the implications of casual, non-permanent forms of employment that have become a common cultural practice in higher education. It proposes that contractual terms of employment have important implications for women and leadership in higher education, since to pursue leadership, usually one must first gain permanency in an organization, in contractual terms. Based on an autoethnographic study by a female academic in a UK higher education institution, the article illustrates that temporary forms of employment, should they be protracted, can stifle leadership aspirations due to lack of career progression opportunities and lead to a sense of alienation from the target community of practice, and even to personal difficulties, such as feelings of isolation and poor self-esteem. The article discusses theoretical and practical implications for women's leadership arising from the findings and makes recommendations for improvements in practice in the higher education sector. The findings and recommendations from this study will also be relevant to other organizational contexts where casual or temporary, fixed term, zero-hours non-permanent forms of employment are common.
Keywords: 350; autoethnography; higher education; women; leadership; identity; habitus; communities of practice